Uniting Through Humour: Navigating Interreligious Dialogue in Indonesia's Cyberspace During Elections - Yuri Nabila Saifatunnisa; Ulfah Wafa Almubarokah; Raihan Aqhsal Arighi; Muhammad Salman Abidin (UIN Sunan Gunung Djati Bandung, 2024)
Purpose: This study explores the role of humour in fostering interreligious dialogue and cooperation within Indonesia’s digital spaces, particularly during the politically charged atmosphere of the 2024 general election. Methodology: Employing netnography, this research focuses on the 'Garis Lucu' (GL) cyberculture, analysing interactions on platforms like Twitter and Instagram to understand how humour mediates religious and political discourse. Findings: The study identifies three main themes: political engagement, political communication, and religious humour. Humour was found to significantly enhance civic engagement and function as a bridge in interreligious communication, easing tensions and fostering a culture of mutual respect and understanding. Research Implications: The findings suggest that digital platforms can serve as effective forums for promoting societal harmony and tolerance through humour, particularly in diverse societies facing political and religious tensions. Originality/Value: This research contributes to the understanding of cyberculture and interreligious dialogue by illustrating how humour can transform potentially divisive political interactions into opportunities for constructive and harmonious exchanges.